Human Herpes Virus 7-related encephalopathy in children - Foiadelli, Thomas; Rossi, Virginia; Paolucci , Stefania; Rovida, Francesca; Novazzi , Federica; Orsini, Alessandro; Brambilla , Ilaria; Marseglia , Gian Luigi; Baldanti, Fausto; Savasta , Salvatore (Acta Biomedica Atenei Parmensis, 2022)
Background: Primary HHV7 infection is almost ubiquitous, and it can present as exanthema subitem. Little is known on the clinical relevance of HHV7 neuroinvasion in immunocompetent children. Methods: We describe 12 patients (median age 9.45 years, 50% males) with acute encephalopathy and active HHV7 infection. In all patients, HHV7-DNA was detected on cerebrospinal fluid (CSF) by RT-PCR. Results: 7/12 patients had meningoencephalitis (two with ADEM and one with MOG antibody-associated CIS); 5/12 showed acute neuropsychiatric symptoms. EEG showed anomalies exclusively in patients with meningoencephalitis. Six patients had RMN anomalies. CSF HHV7 copies ranged between 20 and 3,500 copies/mL (median 66 copies/mL) and mean HHV7 CSF/blood ratio was 0.75. Outcome was favorable in all children, although 3/12 had minor neurobehavioral sequelae. Mean follow-up period of 5.2 months. Conclusions: HHV7 can determine neuroinvasion in immunocompetent children, leading to acute encephalopathy. Blood-brain barrier damage and high CSF/blood viral copies ratio correlated with a more severe presentation. We speculate on the importance of immune-mediated mechanisms in provoking clinical features.